From Efficiency to Indispensability: Rethinking Supplier Resilience What smaller export-oriented countries can learn from Thailand’s GVC experience - Pananond, Pavida (Journal of Multidisciplinary Academic Research and Development (JMARD), 2026)
Resilience has become one of the most invoked concepts in economic policy, yet it means different things to different actors. This article develops a framework for supplier resilience—the form of resilience available to smaller, export-oriented economies whose prosperity depends on participation in chains governed by lead firms headquartered elsewhere. It argues that supplier resilience requires three levels to work together: individual firms, global value chain (GVC) structure, and state policy. Applying this framework to Thailand, the article shows that cost-based positioning is no longer sufficient in an era of geopolitical fragmentation. Building supplier resilience requires three forms of intelligence in concert: geoeconomic intelligence, GVC intelligence, and domestic capability mapping—all translated into resilience-creating value. Thailand’s automotive sector illustrates the cost of misalignment: state policy attracted foreign electric vehicle manufacturers without building domestic supplier capability, weakening rather than deepening structural indispensability. The argument extends to any smaller economy navigating the era of geopolitical tensions. The alignment of resilience at the three levels is critical. The question is no longer whether you can join a global chain. It is whether others can do without you.